Enhancing crystallization and mechanical properties of poly(lactic acid)/milled glass fiber composites via self-assembled nanoscale interfacial structures. (February 2019) - Jing, Mengfan; Sui, Guopeng; Zhao, Jing; Zhang, Qin; Fu, Qiang
Abstract: In this work, renewable poly(lactic acid) (PLA) was mixed with recyclable milled glass fiber (MGF) to improve its crystallization and mechanical properties, which is also good for building a circular economy. To improve the interface interaction between PLA and MGF, silane coupling agent was first adopted as surface modifier, then silica nanoparticles (SiO2 ) with different size (7 nm and 30 nm) were introduced onto the MGF surface via self-assembly strategy (MGF@SiO2 ). It is found that MGF@SiO2 could enhance the crystallization of PLA, even result in a formation of transcrystallization. Moreover, the interfacial interaction could be greatly enhanced via introducing SiO2 (especially 30 nm SiO2 ) onto the fiber surface, which could form mechanical locking. As a result, an obvious improvement of mechanical properties has been achieved. This new approach offers an effective way to adjust the interface structure and the interface interaction, thus helping tailor the performance of polymer/fiber composites.